Organic versus Conventional Agriculture: Comparison of Economic and Environmental Sustainability - Balode Lauma; Pakere Ieva; Luksta Ilze; Blumberga Dagnija (Environmental and Climate Technologies)
Reduction of the level of greenhouse gas emissions from agriculture is one of the most serious issues across the European Union. The dairy industry generates significant emissions from enteric fermentation, manure and long-term storage. The emissions produced depend greatly on factors such as livestock feeding, manure management systems, feed content, and quality. The research aims to evaluate the environmental and economic dimensions of conventional wheat production and dairy farming and compare them in terms of their environmental and economic sustainability. The core element of the sustainability assessment is the construction of the composite sustainability index using data from scientific literature, reports, and statistics. The comparison between organic dairy farming and conventional dairy farming based on sustainability indexes provides valuable insight into the strengths and weaknesses of each system. Organic farming systems present stronger environmental sustainability but require substantial financial support. Organic and traditional farming have their advantages and disadvantages. Policymakers, farmers, and consumers play crucial roles in shaping a future where farming systems can be both productive and sustainable.